Evaluating holistic management in Hwange communal lands, Zimbabwe : an actor-oriented livelihood approach, incorporating everyday politics and resistance - Chatikobo, Tapiwa H. (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.